2019
DOI: 10.1021/acsomega.9b02795
|View full text |Cite
|
Sign up to set email alerts
|

Strategy To Improve Printability of Renewable Resource-Based Engineering Plastic Tailored for FDM Applications

Abstract: This work features the first-time use of poly(trimethylene terephthalate) (PTT), a biobased engineering thermoplastic, for fused deposition modeling (FDM) applications. Additives such as chain extenders (CEs) and impact modifiers are traditionally used to improve the processability of polymers for injection molding; as a proof of concept for their use in FDM, the same strategies were applied to PTT to improve its printability. The filament processing conditions and printing parameters were optimized to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Nano Talc Composites. Rheological properties of the blends and the composites are carried out for 3D printing technology in order to determine the printability, dimension stability, and interlayer adhesion in the 3D printing process [7,18,27]. Figure 4 illustrates complex viscosity (η * ), storage modulus (G ′ ), and loss modulus (G ″ ) from viscoelastic behaviour of the PLA/PBAT blends and the 70/30-nano talc composites.…”
Section: Rheological Behaviour Of Pla/pbat Blends Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Nano Talc Composites. Rheological properties of the blends and the composites are carried out for 3D printing technology in order to determine the printability, dimension stability, and interlayer adhesion in the 3D printing process [7,18,27]. Figure 4 illustrates complex viscosity (η * ), storage modulus (G ′ ), and loss modulus (G ″ ) from viscoelastic behaviour of the PLA/PBAT blends and the 70/30-nano talc composites.…”
Section: Rheological Behaviour Of Pla/pbat Blends Andmentioning
confidence: 99%
“…Cicala et al reported that low viscosity and elasticity of material resulted in flow and dripping of layer deposition that was fallen as poor printing quality [14]. On the contrary, polymers with high viscosities are difficult in printing and lead to inconsistent flow from the nozzle [7]. Qahtani et al found that their printing job failed due to high viscosity and dimensional instability [6].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Papers dealing with the printability of PLA or PHB or different biobased polymer are even rarer. Diederichs et al [ 40 ] investigated how to improve the printability of biobased poly(trimethylene terephthalate) (PTT) with additives such as chain extenders (CEs) and impact modifiers. They were able to prepare 3D printed complete and warpage-free samples because of the modifications made in processing and printing parameters, and with the assistance of additives.…”
Section: Introductionmentioning
confidence: 99%